Permainan Kertas Origami untuk Meningkatkan Penguasaan Kosakata Bahasa Arab Siswa Kelas V SDN Parasrejo 2 Pasuruan - Juharoh Juharoh (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program aimed to improve fifth-grade students’ mastery of Arabic vocabulary, particularly colours and numbers, through origami paper games at SDN Parasrejo 2 Pasuruan. The activity was conducted on 21 September 2025 and involved 25 students through three stages: preparation, implementation, and evaluation. The learning activities included vocabulary introduction, pronunciation practice, matching coloured origami paper with Arabic word cards, and arranging origami pieces according to numerical order. Evaluation was conducted using pre-tests, post-tests, and observation sheets. The results showed that the students’ average vocabulary score increased from 65 in the pre-test to 85 in the post-test, representing a 20-point improvement. Students’ motivation, confidence in answering questions, and active participation also improved during the activity. Origami paper helped students associate Arabic words with colours, quantities, and concrete activities through visual, verbal, and kinaesthetic experiences. Therefore, origami paper games can serve as an affordable, engaging, and practical medium for Arabic vocabulary learning in elementary schools.